How scorza germinated the pentalogy “the silent war” - Guillermo-Buzzi, Juselino (2023)
The works of literary interpretation and hermeneutics are circumscribed within the line of research: Education for social and cultural diversity; more, because they are qualitative formative investigations. The saga of "The Silent War" is not a fictional recreation of the feverish mind of Manuel Scorza Torres, but rather the exasperating testimony that happened to the community members of the central Andes who justly claimed the ancestral possession of their lands before the landlord and the oppressive machinery of state institutions. Scorza makes use of ideology and politics with a laughing sarcasm to unmask the appearance of the tutelary institutions and the characters of which he makes a brief description of the social types and their role and location within the sociopolitical pyramid. Redoble por Rancas is the first of the five novels, in total, that Scorza left behind. According to his own statement by the author, it will be a pentalogy called "The Silent War". Redoble por Rancas becomes a metaphorical and symbolic motif; Territorially, it is the epicenter of the events that are narrated here. The novel Redoble por Rancas ends with an epilogue of a historical nature that leads common readers to reflect on how Peruvian society is stratified and how the excessive interests of a minority affect native communities.